Penceritaan Kisah Alkitab dalam Keluarga sebagai Mandat Pendidikan Iman di Era Digital - Oda Judithia Widianing (Sekolah Tinggi Teologi Berita Hidup, 2026)
The telling of Bible stories is a part of the tradition of passing on the Christian faith to children. However, the massive development of digital technology has brought a significant shift in the pattern of educating Christian faith within the family. The high intensity of relationships with social media has replaced the personal relationships between parents and children. Digital media has replaced essentially the role of parents as the primary narrator of the Bible story. Whereas this is a part of passing on the Christian faith to the next generation. The approach is conceptual, literature-based on scientific sources in databases such as Google Scholar and ResearchGate related to the concept of the telling of Bible stories as a mandate for faith education. This study aims to analyse the concept, theological narrative foundation, and implementation of Bible storytelling in the family in the digital age. The analysis results show that the telling of the Bible story is pedagogical and is a mandate of education from God to every parent. Bible storytelling has a theological narrative foundation. It is about God's faithfulness, God-centred - Christ-centred, with love as the basis of the storytelling. Christian’s parent should critically and creatively tell the Bible story in the digital era.